Development of Arabic-Indonesia Pocket Dictionary to Improve Speaking Skills of Iqro' Stabat Disdit - Muhammad Saleh; Muhammad Aidil Nur; Fatimah Ahmad; Muhammad Ilham (CV. Pusdikra Mitra Jaya, 2023)
For elementary school (SD) level students looking for the meaning of a word in a dictionary is not an easy thing, the Arabic dictionary is different from the Indonesian dictionary, because in the Arabic dictionary if you want to look up the meaning of a word then the dictionary generally has to use the base word, sometimes this is something that is still not understood by students, therefore a dictionary is needed that suits the needs of students so that it is easy to use. Apart from teaching subjects like elementary school, it is also added with Arabic lessons, one of which is. The success of the Arabic learning process is greatly supported by learning media. The research approach used in this study is a qualitative research approach. The initial product development in this study was developed based on the ADDIE stages. to develop learning models compared to other instructional designs. As the name implies, the ADDIE model consists of five stages, namely: Analysis, Design, Development, Implementation, Evaluation. The results of the study show that: 1. Analysis is the initial stage of development research by analyzing the curriculum, student needs, Arabic language subjects, and formulating goals. 2. The feasibility of the Arabic language pocket book media on the basic competence of international trade based on the assessment of material experts and media experts in terms of the feasibility aspects of content, language, presentation, and graphics, 3. The response of SDIT Iqro Stabat students with the Arabic language pocket book shows an average acquisition-an average score of 4.23 for small group trials which are included in the Very Eligible category and an average score of 4.06 for field trials which are included in the Eligible category. 4. Arabic language pocket books can increase student learning motivation by 4.04 which is included in the Increased category.